Islamic Elites’ Perceptions Of Muslim Liyan And Their Impact On Religious Moderation In Islamic Education - Hariyadin, Hariyadin; Kurniawan, Edi (Lembaga Penelitian dan Pendidikan Mandala, 2025)
This study examines how Islamic elites in Jember Regency perceive Muslim Liyan (other Muslims) and how these perceptions influence the development of religious moderation within Islamic education. Using a qualitative phenomenological design, the research explores the subjective meanings underlying intra-Islamic differences through in-depth interviews, participatory observations, and document analysis involving kiai, organizational leaders, and influential preachers. Findings reveal three main typologies of perception: (1) mainstream orthodoxy that prioritizes doctrinal purity, (2) conditional tolerance that accepts diversity within certain boundaries, and (3) rigid exclusivism that rejects the legitimacy of differing groups. These perceptions are shaped by religious educational backgrounds, institutional interests, historical conflicts, and media-driven identity narratives. The study shows that inclusive elite perspectives support the cultivation of religious moderation in Islamic educational institutions, whereas exclusive views tend to foster polarizing attitudes among learners. This research contributes to the discourse on intra-religious exclusivism and offers practical implications for strengthening moderation-oriented curricula, teacher training, and dialogical learning environments within Islamic education.